Gambaran Kebiasaan Jalan Kaki Masyarakat Kota Makassar Tahun 2023 - Yadi Jayadilaga; A.Ulfiana Fitri; Wahyuddin Wahyuddin; Samsiana Samsiana; Irwandy Rachman (Journal of Educational Innovation and Public Health, 2024)
This study aims to examine the effect of walking exercise on the sleep quality of the community in Makassar City. This research is an observational analytic study with a cross-sectional study design. The population in this study was the community in Makassar City, with a sample of the community who accessed the Walking Park in Makassar City. The sampling technique used was non-probability sampling with the accidental sampling method. Out of a total of 399 respondents, it was found that the majority were women aged 21-30 years, unmarried, and had a good perception of their health condition. Most respondents walked 1-2 times a week with a duration of less than 30 minutes. The results of the univariate analysis showed that the majority of respondents were women aged 21-30 years, unmarried, and had a good perception of their health condition. The profile of the walking habits of the respondents shows that the majority do this activity 1-2 times a week with a duration of less than 30 minutes, while only a small portion regularly walk with a duration of 30 minutes or more.